2021
DOI: 10.2172/1825508
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic and mesoscale simulations to determine effective diffusion coefficient of fission products in SiC

Abstract: The silicon carbide (SiC) layer in tristructural isotropic (TRISO) particles serves as the barrier to prevent escape of fission products produced in the fuel kernel. Knowing the diffusion coefficient of fission products through SiC is critical to determining whether fission gas can escape from the particle. It has been observed in experiments that Ag accumulated in grain boundaries and triple junctions in SiC. It is hypothesized that grain boundary diffusion is the primary pathway by which fission products pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In Ref. [5], initial calculations were performed to obtain the effective diffusivity of Nd. Although these calculations were useful to develop the methodology, the effective diffusivity function was fit to the data only for a temperature of 1000 K, and subsequent work showed that the polynomial that was used to fit this data was not readily extensible to other temperatures.…”
Section: Species In Metallic Fuelmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [5], initial calculations were performed to obtain the effective diffusivity of Nd. Although these calculations were useful to develop the methodology, the effective diffusivity function was fit to the data only for a temperature of 1000 K, and subsequent work showed that the polynomial that was used to fit this data was not readily extensible to other temperatures.…”
Section: Species In Metallic Fuelmentioning
confidence: 99%
“…The microstructure is represented with a single order parameter ๐‘. The diffusivity of the bulk phase, represented by ๐‘ โ‰ค 0.1, was set to ๐ท ๐‘๐‘ข๐‘™๐‘˜ = 1.58 ร— 10 โˆ’2 ๐œ‡m 2 /s based on Nd diffusivity through ๐›ผ-U at 1000 K [5].…”
Section: Effective Diffusivity With Isolated Spherical Poresmentioning
confidence: 99%
“…One is that these two slabs are parallel to each other (Figure 1A), while the other one is that they are perpendicular to each other (Figure 1B). For the first structure shown in Figure 1A, the effective diffusion coefficient along the X and Y direction can be described analytically as (Hart, 1957;Jiang et al, 2021)…”
Section: Two Slab Structures For Validationmentioning
confidence: 99%
“…Despite atomistic simulations can give the microscopic mechanism of H interacting with defects, they are hard to predict the effective diffusion coefficient at the microstructural scale due to the limited spatial and time scales. Several analytical models have been developed to estimate the effective diffusion coefficient of the diffusion component in microstructures (Maxwell, 1881;Hart, 1957;Bakker et al, 1995;Chen and Schuh, 2007;Moradi, 2015;Jiang et al, 2021). Maxwell-Garnett et al (Maxwell, 1881;Moradi, 2015) developed a model to predict the effect of the volume fraction of the second phase on the effective diffusion coefficient in a two-phase system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation